UMP research recognised for special awards in MTE - Nor Salwana, Mohammad Idris (2021)
PEKAN, 18 June 2021 - A lecturer of the Faculty of Computing (FK), Universiti Malaysia Pahang (UMP), Associate Professor Ts. Dr. Mazlina Abdul Majid bagged a gold medal and a special award for the Turkish Inventors and Innovators Network Award category through her research titled PISAH Covid Patient Tracking System at Home.